2b-anisotropic Hörmander spaces in cylindrical domains - Los, V.M. (Reports of the National Academy of Sciences of Ukraine, 2018)
We introduce a class of 2b-anisotropic inner product Hörmander spaces in a cylindrical domain. These spaces are obtained by the interpolation with a function parameter between anisotropic Sobolev spaces. A new condition for the continuity of distributions from the introduced spaces together with generalized partial derivatives up to some order is obtained.